Demographic and Mortality Trends across three COVID-19 waves in Kashmir Division, India - Magray, Tahir Ahmad; Nazir, Umar; Rather, Rouf Hussain; Wani, Feroz Ahmad (Asian Journal of Medical Sciences, 2022)
Background: The demographic profile and fatality varied across different waves with the appearance of new variants. Further the trends varied from country to country and within the country. We have analyzed the trends from a selected geographic area. Aims and Objectives: To assess the trends in COVID-19 cases and deaths and to compare the characteristics of three different COVID-19 waves in Kashmir Division. Materials and Methods: It is a cross sectional study based on secondary data. Results: The mean age of deaths increased from 64.53 years in first wave to 65.02 years in the second wave and further to 69.23 years in the third wave (p-value = 0.006). An overall CFR of 0.85% was observed in our population with a maximum case fatality of 1.67% in first wave followed by 0.79% in second wave and only 0.13% in third wave (p < 0.0001). Lowest CFR of 0.04% was observed in the age group of <20 years and maximum CFR of 6.12% was observed in the subjects with age more than 60 years. It was also observed that the CFR increased with the increase of age across all the three waves (p < 0.0001). Conclusion: Our study suggests that the Case Fatality Ratio declined with time despite new variants appearing which spread at very fast rate. The mortality remained higher in elderly and in males in all the three waves.